Citalopram-induced sleep bruxism in a breastfed infant: A case report - Akbarzadeh, Farzad; Behravan, Ghazal; Modaresi, Farzaneh; Eslamzadeh, Mahboubeh (Frontiers in Psychiatry, 2023)
Bruxism associated with antidepressant use is an under-recognized phenomenon. The use of citalopram has gained wide acceptance in the treatment of depression and anxiety disorders; however, the consumption of this medication during lactation and pregnancy has not been carefully characterized. There are limited studies about its side effects in the breastfeeding period. Here, we report a rare case of citalopram-induced sleep bruxism in a 9-month-old female breastfed infant whose mother used SSRI agent citaloporm for her anxiety disorder. Within 2 weeks of initiating her citalopram treatment, with a starting dose of 10 mg/day, the patient reported sleep bruxism in her infant. Thorough examinations of the infant were performed and no abnormal finding was reported. After ruling out other possible causes, the new-onset bruxism symptoms were attributed to the mother’s recent use of citalopram, which was discontinued thereafter. The infant’s symptoms of bruxism disappeared following the discontinuation of the medication by her mother. These findings and similar reports could draw more attention to bruxism or other possible symptoms in breastfed infants of mothers consuming psychotropic medications.